Pengaruh Partisipasi Pemakai Terhadap Kepuasan Pemakai Dalam Pengembangan Sistem Informasi Dengan Faktor Kontinjensi Dan Pengaruhnya Terhadap Kinerja Pemakai Pada Perusahaan Menengah Di Kalimantan Timur - Aplonia Lau, Elfreda (Program Doktor Ilmu Ekonomi, 2014)
This study examines behavioral accounting on the basis of the theory of information systems. Respondents in this study were 200 respondents of the users of information systems in medium enteprise in East Kalimantan. The results indicate that user participation in the development of information systems influence user satisfaction in information system development, although the magnitude of the effect is 9%. The result indicates that user - developer communication, task complexcity, system complexcity, user influence, organisation culture moderated the effect of user’s participation on user’s satisfaction in information system development. It was also found that top management support acts as independent predictor on user’s satisfaction in information system development. User-developer communication having positive effetc on user’s satisfaction in information system development. User influence having negative effect on user’s satisfaction in information system development. Task complexcity and system coplexcity having negative effect on user’s satisfaction in information system development. Organizational culture having positive effect on user’s satisfaction in information system development. User’s satisfaction having positif effect on user’s performance in information system development.Keywords: User’s Participation, Top Management Support, Communication User-Developer, Task Complexity, System Complexity, User’s Influence, Organizational Cul-ture, User’s Satisfaction and User’s Performance.